The Secret March - Thunig, Marco; Landwehrjohann, Max (Satura, 2022)
We’re in a cold sweat when we get out of our bunk beds. We brush our teeth with water by Nestlé, walk up to the platoon in the pale morning light, smoke knock-off Marlboros from faded packs. Maharadscha, the Brazilian label says. Christiano, whose actual name is Christian, starts by letting his chainsaw roar, clearing a path through the green as the vanguard for the shovel-mounted vehicles. He once said that he’s not going to cut his hair as long as he’s here and that he wants everyone to know. Christiano always wears this red bandana over his black curly locks, and sports a mustache and a wooly 70s chest, which, after eleven and a half hours in the weeds, turns into a sticky, brown-grayish pulp.